2020
DOI: 10.1111/tid.13283
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns and incidence of adenovirus infection in allogeneic hematopoietic cell transplant recipients: Multicenter survey of transplant centers in the United States

Abstract: Background Adenovirus (AdV) is increasingly recognized as a threat to successful outcomes after allogeneic hematopoietic cell transplantation (allo‐HCT). Guidelines have been developed to inform AdV screening and treatment practices, but the extent to which they are followed in clinical practice in the United States is still unknown. The incidence of AdV in the United States is also not well documented. The main objectives of the AdVance US study were thus to characterize current AdV screening and treatment pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…As incidence is low, there is no defined treatment regimen for a HAdV hepatitis [ 1 , 4 , 23 ]. Published guidelines focus on treatment recommendations for patients following SCT [ 5 , 6 , 9 , 16 , 23 ]. Accordingly, immunosuppression should be reduced as T-cell recovery contributes to viral clearance [ 4 , 5 , 8 , 9 , 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As incidence is low, there is no defined treatment regimen for a HAdV hepatitis [ 1 , 4 , 23 ]. Published guidelines focus on treatment recommendations for patients following SCT [ 5 , 6 , 9 , 16 , 23 ]. Accordingly, immunosuppression should be reduced as T-cell recovery contributes to viral clearance [ 4 , 5 , 8 , 9 , 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Published guidelines focus on treatment recommendations for patients following SCT [ 5 , 6 , 9 , 16 , 23 ]. Accordingly, immunosuppression should be reduced as T-cell recovery contributes to viral clearance [ 4 , 5 , 8 , 9 , 16 , 23 ]. Patients 1 and 2 did not have immunosuppression when viremia evolved, or they were on local budesonide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of HAdV infection ranges between 2% and 15% in allo‐HSCT patients, in whom it manifests as cystitis, gastroenteritis, pneumonia, encephalitis, hepatitis, or disseminated systemic infection, and is frequently encountered after Herpes simplex virus and CMV 12‐16 . Previous reports have shown that the risk factors for post allo‐HSCT HAdV infection include GVHD of grade III or IV, detection of HAdV at two or more sites, T cell‐depleted grafts, unrelated donors, cord blood transplants, haplo transplants, Alemtuzumab, and ATG administration.…”
Section: Discussionmentioning
confidence: 99%